Preparation of a cereal bar containing bocaiuva: physical, nutritional, microbiological and sensory evaluation - Munhoz, Cláudia Leite; Guimarães, Rita de Cássia Avellaneda; Nozaki, Vanessa Tais; Sanjinez-Argandoña, Eliana Janet; Hiane, Priscila Aiko; Macedo, Maria Lígia Rodrigues (Acta Scientiarum. Technology, 2014)
Regional fruit have been increasingly used in recent years in the preparation of foodstuffs because besides promoting the biome preservation, it is obtained differentiated and value-added products. This study aimed to prepare cereal bars containing pulp and kernel of bocaiuva and determine the nutritional quality, assess the acceptability, and microbiological quality. Two formulations of cereal bar were prepared with pulp dehydrated by osmoconvection and kernel of bocaiuva. The formulations were analyzed as for the texture, color analysis, proximate composition, fatty acids profile, mineral, microbiology and sensory evaluation. Cereal bars presented on average, in g 100 g-1, 4.83 moisture, 8.01 protein, 12.93 lipids, 1.30 ash, 53.75 total carbohydrate, 19.78 fiber and 363.41 kcal 100 g-1 total caloric value. Bars represented a source of calcium and iron and had a high content of oleic acid, average of 20 g 100 g-1 total lipids. In the microbiological evaluation, cereal bars have met the standards set by the legislation, being suitable for consumption. As for the attributes evaluated in the sensory analysis, all showed mean values above 6, considered acceptable for consumption. The use of bocaiuva may contribute to highlight differentiated taste and appearance, emphasizing the use of native fruits in the preparation of new products. Â